Bulungan Delta Clastic Wedges - Winaldy Winaldy (Ikatan Ahli Geologi Indonesia, 1999)
Most of the gas and oil fields within the greater N.E Kalimantan basin are discovered in Tarakan subbasin. The Tarakan subbasin, the most productive subbasin, developed significantly during Middle Miocene to Pliocene when accommodation space for an increased volume of deltaic sediments was created due to a combination of basin subsidence and gravity induced listric faulting. However, the uplift of the western basin margin that had begun after Late Early Oligocene and continued into Miocene created shallower depositional conditions in the northern part of the basin (Tidung and Tarakan subbasins). The newly emergent area to the west formed constructive deltas that prograded from west to the east. Nevertheless, in the southern area (Berau and Muara subbasins) the depostion was under stable condition whereby platform carbonates and deeper marine sediments filled the region.